Portugal’s rising research in architecture and urbanism: the influence of international research centers and authors - D'Almeida, P. B.; Marat-Mendes, T.; Toussaint, M. (Journal of Urban History, 2022)
In the early 1960s, Portugal saw a rise in scientific research on architecture and urbanism at the National Laboratory of Civil Engineering (Laboratório Nacional de Engenharia Civil; LNEC), fundamental to support the Government in establishing a national program for housing, which continued until the fall of the Dictatorship in 1974. Lacking tradition in scientific studies in architecture and urbanism, a group of young architects with knowledge of references from international researchers and research centers gathered encouragement and opportunities to develop their own research works and methodologies and, later, to question the application of such scientific methods. This article aims to identify and discuss the strategies and methodologies explored to develop these seminal researches, retrieving and reappraising LNEC’s archived documents and oral testimonials from former researchers. We aim at exposing the foundations of Portuguese scientific research on architecture and urbanism and its contributions to an international audience